Role of the Surgical Method in Development of Postoperative Cholangiocarcinoma in Todani Type IV Bile Duct Cysts - Hong-tian Xia; Tao Yang; Bin Liang; Jian-ping Zeng; Jia-hong Dong (Gastroenterology Research and Practice)
Background. Our purpose was to investigate the association between the surgical approach for Todani type IV cysts and subsequent malignancy rate. Methods. The records of patients who received cyst excision from 1994 to 2013 were analyzed retrospectively for the following data: demographics, presenting symptoms, postoperative outcomes, malignant transformation, and follow-up reexaminations, including imaging, laboratory, and tumor marker tests. Results. Seven of the 196 patients initially treated at our hospital developed postoperative biliary malignancy, and the surgical approaches were extrahepatic bile duct cyst resection combined with hilar cholangioplasty and Roux-en-Y cystojejunostomy (n=5), and intra- and extrahepatic bile duct cyst resection and Roux-en-Y hepaticojejunostomy (n=2). The overall malignancy rate was 3.6% (7/196). Forty-eight patients initially treated at other hospitals developed malignancy postoperatively: 15 (31.2%) remained untreated and 33 (68.8%) had undergone incomplete resection procedures. Because Todani type IV cysts were seen in 268 patients, the postoperative malignancy rate of this group of patients was 12.3% (33/268). Conclusions. Radical resection of both intra- and extrahepatic cysts combined with hepatic resection and Roux-en-Y hepaticojejunostomy is associated with a reduced risk of subsequent cancer development. Procedures in which radical cyst excision is not performed are associated with a greater risk of subsequent malignancy.